Design and control of power converters for wireless power transfer system - Ang, Wilson Han Chuan (Nanyang Technological University, 2021)
Wireless power transfer systems allow the transfer of power without the use of cables in a safe and convenient manner and it has been an area of interest for R&D regarding charging applications for devices such as bio-medical implants, electrical vehicles and mobile devices. One crucial component of a wireless power transfer system are the power converters that converts Direct Current to Alternating Current and vice versa. The performance of the power converters will affect the characteristics of the system such as its efficiency, output power etc. The performance of the power converters is affected by its design, topology and control methods. Thus, it is essential to determine the optimal design, topology and control methods by comparing certain aspects such as their cost, efficiency, complexity using relevant research materials and analysis of plots derived from model simulations. Another crucial component of a wireless power transfer system are the coils. Misalignment of the coils can occur easily and it reduces the output power of the system thus it is essential to devise a method of mitigating the effects of coil misalignment on the output of the system. This report lays out the details of the final year project such as introduction, objective, scope, literature review, theoretical analysis of inverters, rectifiers, phase shift modulation control method, experiment design process for the IPT system and the various experiments carried out for the IPT system.